Empowerment of Village Owned Enterprises in Lapodi Village Buton Regency - Fariz Mustaqim Fariz; I Wayan Sujana; Ernawati Malik (Universitas Muhammadiyah Purwokerto, 2023)
Villages are the leading government agents for economic development. The village becomes a government representative who deals directly with the community. The central government mandates village governments to independently utilize the potential resources in their areas. One of them is through village-level economic institutions, namely Village-Owned Enterprises. BUMDES was born as a new approach to improve the village economy based on the needs and potential of the village. The birth of Law Number 32 of 2004 concerning Regional Government, has encouraged villages to develop Village-Owned Enterprises (BUMDes) in accordance with the needs and potentials of each village in order to increase community income and original village income. This Community Service activity was carried out in Lapodi Village, South Buton Regency Overall, this community service activity was carried out on December 20, 2022. The activity partner is BUMDes Desa Lapodi. This activity is carried out in two stages, namely preparation and socialization. The existence or position of BUMDes is considered very effective in exploring the local potential of the village. BUMDes offer great potential because of the existence of mutually sustainable village regulations. BUMDes are also a place to explore the potential of local villages. Therefore, the existence of BUMDes is very urgent to achieve the goal of a prosperous independent village. Therefore, the most appropriate preparations are focused on socialization, education and training of interested parties to improve the standard of living of rural communities. Thus, the existence of BUMDes aims to encourage the dynamics of economic life in rural areas. The role of the village government is to build relationships with the community to achieve the fulfillment of Minimum Service Standards (SPM) as part of efforts to build a stronger village community (development-based community). Based on the results of the study, it is known that BUMDes are an internal forum Exploring local potential is very important. In the realization stage, the establishment and development of BUMDes need further attention from the government. Therefore, it is necessary to revitalize BUMDes to facilitate and protect the formation of business units in order to strengthen capacity.